Splines with Minimal Defect and Decomposition Matrices - Makarov, A. A. (Communications in Mathematics and Applications, 2012)
Finite-dimensional space of twice continuously differentiable splines on a nonuniform grid are considered. We also construct a system of linear functionals biorthogonal to the splines and resolve an interpolation problem generated by this system. We derive the decomposition matrices on an interval and on a segment for the space of forth order (third degree) splines associated with infinite and finite nonuniform grids respectively.